(untitled) (Third Sector Social Economic Review, 2019)
The present study is designed to investigate how power attaining strategies are handled in fairy tales and cartoons and passed on to children. In the first step of the research, for 3 years PhD students who took “Power and Politics in Organizations” course in Marmara University Institute of Social Sciences Management and Organization Department were asked to indicate the tales and / or cartoons that remind them of 17 power attaining strategies that were handled in class. Each student was asked to find at least 3 fairy tales or cartoons and explain in which part of the fairy tale or cartoon the strategy takes place. In this context, 40 students linked 60 fairy tales and/or cartoons with power strategies. After eliminating similar ones, 9 fairy tales and 12 cartoons were left. The representation of power through heroes in fairy tales and cartoon was analyzed through this selected sample. The results of the study reveal that “power” is the main theme hidden in many fairy tales that we read and cartoons that we watched in our childhood. Since almost all of the examples are given out of cartoons, the results also reveal that fairy tales do not take much place in the world of young people.